Prediction of pumping pressure by means of new tribometer for highly-workable concrete. (March 2015) - Feys, Dimitri; Khayat, Kamal H.; Perez-Schell, Aurelien; Khatib, Rami
Abstract: Predicting pressure during pumping has received special attention in recent years. For conventional vibrated concrete (CVC), Kaplan et al. developed a tribometer to characterize the properties of the lubrication layer that is formed when concrete flows in a pipeline, to predict pressure. As this approach is limited to CVC, a new tribometer and data treatment procedure were recently developed by the authors, extending this approach for highly-workable concrete. This paper describes full-scale pumping tests undertaken to validate the tribological properties of the lubricating layer, determined using the novel tribometer. The program involved pumping 25 concretes, including 18 self-consolidating mixtures in a 30 m long loop. The paper describes the pump, circuit, pressure and flow rate measurements, and the employed rheometer and tribometer, which are needed to predict pumping pressure. The results show that the model developed by Kaplan et al. accurately predicts pressure losses, confirming that the developed tribometer delivers accurate results for highly-workable concrete. Furthermore, it is shown that the assumption employed for CVC where the concrete flows as a plug surrounded by the lubrication layer is not always true, as the occurrence of plug flow depends on pumping characteristics, pipe diameter and concrete rheological and tribological properties.